Endoscopic Ultrasound-Guided Antegrade Radiofrequency Ablation and Metal Stenting With Hepaticoenterostomy for Malignant Biliary Obstruction: A Prospective Preliminary Study. Issue 10 (15th October 2020) - Inoue, Tadahisa; Ibusuki, Mayu; Kitano, Rena; Kobayashi, Yuji; Ohashi, Tomohiko; Sumida, Yoshio; Nakade, Yukiomi; Ito, Kiyoaki; Yoneda, Masashi
Abstract : OBJECTIVES: Endobiliary radiofrequency ablation (RFA) for malignant biliary obstruction is a promising option for improving biliary stent patency, but its efficacy and safety with endoscopic ultrasound (EUS)-guided biliary drainage are uncertain. We examined the feasibility of EUS-guided hepaticoenterostomy with antegrade stenting (EUS-HEAS) and RFA in patients with unresectable malignant biliary obstruction. METHODS: This was a prospective, single-center, single-arm, preliminary study. Twenty patients who met the eligibility criteria for inclusion between August 2018 and January 2020 were enrolled. We evaluated the technical success, functional success, recurrent biliary obstruction (RBO), and adverse events other than RBO associated with EUS-HEAS with RFA. RESULTS: The technical and functional success rates were both 80% (16/20). The procedure was unsuccessful in a total of 4 patients due to failure to insert the RFA catheter through the fistula (2 patients) or failure to pass the RFA catheter through the stricture (2 patients). Early and late adverse events other than RBO occurred in 10% (2/20) and 13% (2/16) of subjects, respectively. The RBO rate was 25% (4/16), and the median time to RBO was 276 days. The success rate of endoscopic reintervention using hepaticoenterostomy was 100% (4/4). DISCUSSION: This preliminary study showed that EUS-HEAS with RFA achieves good results but RFA catheter insertion can be difficult. Further evaluation and device improvements are warranted.